PENGGUNAAN PRESENT PERFECT TENSE BAHASA INGGRIS OLEH SISWA SMK KESEHATAN BAKTI NUSANTARA GORONTALO (SEBUAH ANALISIS KESALAHAN) - Antula, Pungky Wulansakti (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
I. Abstrak This research is entitled â€œPenggunaan Present Perfect Tense Bahasa Inggris oleh Siswa SMK Kesehatan Bakti Nusantara Gorontalo (Sebuah Analisis Kesalahan)â€. The objectives of this research are to identify and classify the errors made by students of SMK Kesehatan Bakti Nusantara Gorontalo and analyze them based on Ellisâ€™ (1997) theory about error analysis. Ellis categorizes three types of errors in the learnerâ€™s language namely omission, misinformation, and misordering. The writer used descriptive method in this research. The writer used a writing test consisting of present perfect tense material in order to get the data from the students.Â  The data were collected from two classes of SMK Kesehatan Bakti Nusantara Gorontalo in Nursing 1 and Nursing 2 which have studied about present perfect tense. There were 21 students in each class who took the test. The results of this research show that there are several errors that students made in the use of present perfect tense. The errors are classified into omission, misinformation, and misordering. The errors of omission include omission of verb ending in regular verb, omission of the auxiliary verb have/has, omission of preposition since and for, and omission of subject. The errors of misinformation include misinformation of past participle form of regular verb, misinformation of past participle form of irregular verb, misinformation of the auxiliary verb have/has, misinformation of the preposition since and for and misinformation of object. The errors of misordering include misodering of have/has in a question, misordering of preposition since and for, misordering of adverb already and misordering of conjuction yet. This is research supports Ellisâ€™s (1997) theory about error analysis. Keywords: Error Analysis, Present Perfect Tense, Vocational School Students